Effectiveness of Police Services in Handling Community Reports in the Minahasa Regency Police Force (Case Study of Minahasa Regency Police) - Jeane Mantiri,; Abdul R. Dilapanga,; Tri N. Noviantoro,; Enjelhart Hansiden Polii, (Technium Social Sciences Journal, 2023)
The purpose of this study is to illustrate the effectiveness of the police in handling community reporting in the Minahasa district resort police. The method used in this study is qualitative method. This research was carried out by observation located at the Minahasa Regency Police and conducting an interview with one of the SPKT officers at the Minahasa Resort Police and taking documentation to complete the data collection. The results of the study based on the predetermined research focus are: 1) Public service mechanism, 2) Responsiveness, 3) Transparency, 4) Speed, 5) Accuracy, it was found that the police service in handling community reporting at the Minahasa Resort Police has been running effectively and in accordance with existing service procedures and in accordance with applicable laws and regulations.